Making sense of the doxastic approach to thought insertion. - López-Silva, Pablo (Synthese, 2024)
With a higher prevalence in schizophrenia, delusions of thought insertion (TI) are regarded as one of the most severe symptoms of psychosis. Patients suffering from TI report that external agents are able to place thoughts into their minds or skulls. A version of the doxastic approach characterizes delusions as abnormal beliefs rooted in anomalous experiences. Nonetheless, the exact role of these experiences in determining the content and the way in which delusional beliefs are fixated is still under debate. While endorsement models claim that the abnormal experience comprises the very content of the delusional beliefs, explanationist approaches claim that delusional beliefs emerge as explanations for abnormal experiences with less specific content. This paper combines conceptual analysis with phenomenological data to examine the merits of both endorsement and explanationist approaches to TI. I propose that potential solutions to the dispute could lay in finding a middle ground between the two approaches, and non-exhaustive ways in which hybrid doxastic approaches to TI could be formulated.